From Global to Local-Modeling Low Emissions Development Strategies - De Pinto, Alessandro (2015)
IFPRI Policy Seminar “Climate Change & Food Security: Challenges and Options at Global and National Scales” on November 10, 2015. Presentation by Alex De Pinto.